(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the characteristics of anemia and the outcomes of erythropoiesis-stimulating agent (ESA) therapy in patients with end-stage chronic kidney disease (CKD) undergoing maintenance hemodialysis (MHD) at Hai Phong University of Medicine and Pharmacy Hospital. Subjects and Methods: A cross-sectional descriptive study with a 6-month longitudinal follow-up was conducted in patients with end-stage CKD (according to KDIGO 2024) undergoing maintenance hemodialysis at the Department of Nephrology and Dialysis, Hai Phong University of Medicine and Pharmacy Hospital, from October 2025 to April 2026. Results: The study included 90 patients with a mean age of 57.66 ± 14.37 years. The mean hemoglobin (Hb) level was 92.65 ± 15.90 g/L; 88,9% of patients had functional iron deficiency. After 6 months of ESA therapy, Hb levels increased significantly (100.18 ± 19.5 g/L; p = 0.001). The rate of achieving target Hb was 51.1%, and the good response rate was 41.1%. The mean erythropoietin resistance index (ERI) was 15.08 ± 6.65. Multivariate regression analysis showed that serum albumin was the only independent factor associated with ESA response (p < 0.05). Conclusion: ESA therapy significantly improved hemoglobin levels; however, the rate of achieving target Hb remains limited. Serum albumin was independently associated with ESA response, suggesting the important role of nutritional status in treatment effectiveness.